Optimized rank-based key management for energy-efficient routing in wireless sensor networks for IoT applications - Hussain, Muzammil; Hussain, Mudassar; Aamer, Najmuddin; Shaikh, Farhan (Discover Internet of things, 2025)
The growing use of Wireless Sensor Networks (WSNs) in Internet of Things (IoT) applications requires innovation in energy-efficient and secure communication protocols to improve network functionality and lifetime. Legacy routing protocols struggle to achieve an equilibrium between energy usage, security, and information accuracy, resulting in excessive node failure rates and transmission errors. Compared to previous methods, this candidate RK-EFCRP is the first to combine a rank-based dynamic key update protocol with the hierarchy clustering hierarchical structure of the hybrid RK-tree, and can comprehensively optimize both routing and cryptography security, within the same lightweight structure. To solve these problems, this paper presents an enhanced Rank-Based Key Management for Energy-Efficient Cluster-Based Routing Protocol (RK-EFCRP) which implements a new hierarchical clustering method with Adaptive Cluster Head (CH) selection and a novel rank-based key assignment scheme to enhance the system’s stability, security, and energy efficiency. The effectiveness of RK-EFCRP is compared with the last mile safety routing for low power WSN (Safety-RPL) protocol, Hybrid Blockchain Enabled Energy Efficient Routing (HBEER), Secure and Energy Efficient Hierarchical Routing (SEHR), and Secure and Energy Aware Multi-Hop Hierarchical Routing (SEAMHR) protocol using energy efficiency, security strength, latency, and packet delivery ratio (PDR), and overall network lifetime as key performance indicators (KPIs). Experimental results demonstrate that RK-EFCRP significantly reduces energy consumption to 6.13 J, outperforming other protocols like SEAMHR (11.20 J). Additionally, RK- EFCRP enhances security strength to 97.5%, surpassing SEAMHR (85%) and HBEER (78%) as well. Moreover, unlike existing protocols that operate between 1.5 and 2.3 ms, RK-EFCRP reduces latency to 0.12 ms. The protocol has an improved PDR of 97.8%, surpassing Safety-RPL (91.5%) and the other models. Lastly, network lifetime is improved and extended to 3200 rounds compared to SEAMHR's (2100 rounds). From these results, it is evident that RK-EFCRP optimizes the balance of energy efficiency, security, and data reliability makes RK-EFCRP performing well for WSN based IoT applications. Rank based key allocation along with dynamic CH selection provides effective solutions to security holes and cuts down failure transmission while boosting overall network performance. This research facilitates the next steps towards intelligent and secure WSN based IoT systems with flexible and robust network structures.